The Role of Print Media in Shaping Public Health Outcomes: A Comprehensive Review (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This theoretical study investigates how health-related material in print media affects public health by synthesising current data to grasp its influence in determining public health results. Even with the digital revolution, print media including newspapers, periodicals, and pamphlets remains a major source of information. Key topics include the spread of health information, the way health concerns are framed, and the impact on public perspective and behaviour are underlined in the review. Research show that print media may influence health policy debate, increase knowledge of health concerns, and encourage good practices. Still, these results are much influenced by the accuracy, bias, and depth of the material. Print media's health-related material reflects more general social, economic, and political settings, therefore impacting its presentation and reception. Moreover, the different degrees of media literacy among the people help to control the influence of such material. The evaluation also covers ethical obligations of print media in health communication as well as the possibility of false information. This study offers a complete framework for comprehending the intricate interaction between print media and public health by combining theoretical viewpoints from psychology, public health, and communication studies. The results underline the importance of planned, evidence-based health communication in print media to improve its favourable influence on public health outcomes.